THE EFFECT OF HUMAN RESOURCE COMPETENCE AND CHARISMATIC LEADERSHIP ON FINANCIAL ACCOUNTABILITY AT ISLAMIC BOARDING SCHOOLS IN BIREUEN REGENCY - Fikri Rijal; Damanhur Abbas; Naz’aina (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2022)
This study examined and analyzed the effect of human resource competence and charismatic leadership on financial accountability in Islamic boarding schools in the Bireuen Regency. This study used primary and secondary data. The primary data was obtained by using a questionnaire to 98 respondents in Islamic boarding schools in Bireuen Regency, and the secondary data was obtained through online news, articles, and other news sources related to the required data. In addition, researchers also conducted observations. The data analysis method used was a structural method based on variance, namely Partial Least Square (PLS). The results showed that the competence of human resources and charismatic leadership positively influenced the financial accountability of Islamic boarding schools in the Bireuen Regency.